2022
DOI: 10.1021/acsomega.2c04456
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Insight into Allosteric Regulation of Kir Channel Activity

Abstract: Potassium (K + ) channels are regulated in part by allosteric communication between the helical bundle crossing, or inner gate, and the selectivity filter, or outer gate. This network is triggered by gating stimuli. In concert, there is an allosteric network which is a conjugated set of interactions which correlate long-range structural rearrangements necessary for channel function. Inward-rectifier K + (Kir) channels favor inward K + conductance, are ligand-gated, and help establish resting membrane potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 69 publications
(175 reference statements)
0
13
0
Order By: Relevance
“…CG molecular dynamics (CGMD) simulations were performed in tandem to complement the NMR data analysis. We previously observed in MD calculations that residues involved in the allosteric network could be mutated to impact PG residency time and residue–residue contacts throughout the channel . Thus, we hypothesized that we might observe interesting phenomena in CGMD PG titrations as well.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…CG molecular dynamics (CGMD) simulations were performed in tandem to complement the NMR data analysis. We previously observed in MD calculations that residues involved in the allosteric network could be mutated to impact PG residency time and residue–residue contacts throughout the channel . Thus, we hypothesized that we might observe interesting phenomena in CGMD PG titrations as well.…”
Section: Resultsmentioning
confidence: 91%
“…When these residues are mutated to glutamine, the channel is closed and inactive. Based on the mutational analysis in CGMD simulations, we also suggested that residues proximal to this arginine pocket may also play a role, either during the first steps of allosteric communication or as secondary residues supporting the pocket itself . However, experimentally, we did not have a complete picture of lipid–protein interactions in the open-activated state of the channel.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations